Effect of Physical Activity Level and Behavioral Regulations in Exercise on Successful Aging - Erbas, Ulfet (Progress in Nutrition, 2021)
Study Objectives: The COVID-19 pandemic not only changed many of our routines but also led to significant changes in our health and life habits. In this process, which is called the new normal, the aim of this study was to examine the effect of physical activity level and behavioral regulation in exercise on successful aging in adult individuals. Methods: A total of 484 volunteers, 202 females and 282 males, aged between 52 and 74, living in Ankara province participated in the study voluntarily. In the study, International Physical Activity Level Questionary-Short Form, Successful Aging Scale, and Behavioral Regulations in Exercise Scale-2 were used as data collection forms. The distribution normality was tested with kurtosis-skewness values. In the analysis of the data, descriptive statistics, Regression Analysis, Independent Samples t test, and One-way ANOVA were used. Results: There was a moderately significant positive correlation between the participants’ mean scores of behavioral regulations in exercise and their mean scores of successful aging (r = 0.486). Examination of the relationship between Behavioral Regulations in Exercise and the sub-dimensions of the Successful Aging Scale showed a moderate positive relationship with all sub-dimensions. On the other hand, there was no significant relationship between physical activity level and successful aging. According to the results of multiple regression analysis, behavioral regulations in exercise significantly predict successful aging. In addition, participants’ physical activity levels and successful aging scale scores differ in terms of gender and income status. Conclusion: Exercising causes older individuals to have a healthier body and the chance of living with a better outlook. In addition, individuals can develop more positive emotions in coping with life and problems, which explains the effect of exercise on successful aging.